Improving Students' Vocabulary Mastery By Using What'sMissing Technique At The Sixth Year Of SD N 3 Nogosari In2011/2012: An Action Research - Ambarwati, Ambarwati (2012)
This study aims at describing whether What's Missing technique can improve the students' vocabulary and how the implementation of the technique in the teaching vocabulary at the sixth grade of SD Negeri 3 Nogosari. In this research, the writer carries out an action research. The action procedures are planning, acting, observing, and reflecting. In the classroom action research, the writer uses test, observation, interview, and collaborates them to collect the data. The sources of data are the activities of improving the vocabulary mastery using what's missing technique, the English teacher, and the students as subject, the teacher's lesson plan. This research was conducted in the fourth grade of SD Negeri 3 Nogosari, Boyolali. The Implementation of improving vocabulary mastery using what's missing technique consists of the students' achievement in memorizing, pronouncing, and spelling the words. In memorizing the students must remember what is picture that was moved by the teacher. In the pronouncing the students must said what word that they was remembered is. After pronouncing the students should spell the word by written form in the blackboard. To know the result of improving vocabulary mastery using what's missing technique, the writer give three kinds of test, namely: pre-test, post-test I, and post-test II. The test consists of pronunciation, understanding meaning, and spelling. The mean score of the pretest is 48,81, while the mean score of the post test I is 59,19. Mean score of the post-test II is 82,25. So, there is a significant improvement of the students' vocabulary mastery before and after the research done. Therefore it can be concluded that teaching vocabulary by using visual aids through pictures could improve the students' vocabulary mastery.